Pengaturan Hukum Laut Internasional dan Nasional dalam Pencemaran Lingkungan Hidup di Perairan Indonesia Akibat Sampah Plastik - Irwan Sasradinata; Agung Pramono; Lufsiana Lufsiana (Universitas Medan Area, 2023)
Garbage in the waters causes pollution and damage to the environment and aquatic ecosystems and endangers human health. Plastic waste is a component that is difficult to decompose by natural processes so that it is harmful to aquatic ecosystems and human health. The problems examined in this paper are regulation the International Law of the Sea concerning the protection of the marine environment and the regulation of National Law in the prevention, reduction and management of environmental pollution in Indonesian waters due to plastic waste and how to enforce the law in Indonesia on environmental protection in Indonesian waters with regard to plastic waste. The research method used in this study is a normative legal research method, where the primary data is taken from international treaties and laws and regulation that have relevance in this research. The result of this study indicate that the regulation of International Law on the protection of a country’s marine environment is further regulated in the 1972 Stockholm Declaration, 1982 UNCLOS, International Maritime Organization and others, so that through these regulations countries can protect the marine environment, take all necessary actions and take responsibility. Responsible for the pollution of the marine environment, especially due to plastic waste. National Law Enforcement in Indonesia is regulated in Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation.